Cari p 1, a Novel Polygalacturonase Allergen From Papaya Acting as Respiratory and Food Sensitizer - Sarkar, Moumita B.; Sircar, Gaurab; Ghosh, Nandini; Das, Abhishek K.; Jana, Kuladip; Dasgupta, Angira; Bhattacharya, Swati G. (Frontiers in Plant Science, 2018)
Papaya has been reported to elicit IgE-mediated hypersensitivity via pollen inhalation and fruit consumption. Certain papaya sensitive patients with food allergy were found to experience recurrent respiratory distresses even after quitting the consumption of fruits. This observation prompted us to investigate the allergens commonly present in fruits and pollen grains of papaya. A discovery approach consisting of immunoproteomic detection followed by molecular characterization led to the identification of a novel papaya allergen designated as Cari p 1. This allergen was detected as a 56 kDa IgE-reactive protein from pollen as well as fruit proteome through serological analysis. The protein was identified as an endopolygalacturonase by tandem mass spectrometry. Full length Cari p 1 cDNA was isolated from papaya pollen, cloned in expression vector, and purified as recombinant allergen. The recombinant protein was monomeric and displayed pectinolytic activity. Recombinant Cari p 1 reacted with IgE-antibodies of all the papaya sensitized patient sera. In addition to IgE-reactivity, rCari p 1 displayed allergenic activity by stimulating histamine release from IgE-sensitized granulocytes. CD-spectroscopy of rCari p 1 revealed the presence of predominantly β-sheet characters. The melting curve of the allergen showed partial refolding from a fully denatured state indicating the possible presence of conformational IgE-epitopes characteristic of inhalant allergens in addition to the linear IgE-epitopes of food allergens. The expression of this allergen in papaya fruits was detected by immunoblot with anti-Cari p 1 rabbit IgG and reconfirmed by PCR. In an in vivo mouse model, rCari p 1 exhibited a comparable level of inflammatory responses in the lung and duodenum tissues explaining the dual role of Cari p 1 allergen in respiratory sensitization via pollen inhalation and sensitization of gut mucosa via fruit consumption. Purified rCari p 1 can be used a marker allergen for component-resolved molecular diagnosis. Further immunological studies on Cari p 1 are warranted to design immunotherapeutic vaccine for the clinical management of papaya allergy.